A comprehensive spatially-explicit analysis of agricultural landscape multifunctionality using a New Zealand hill country farm case study. (December 2022) - Tran, Duy X.; Pearson, Diane; Palmer, Alan; Gray, David; Lowry, John; Dominati, Estelle J.
Abstract: CONTEXT: Multifunctionality can refer to the capacity of a landscape to provide a wide range of ecosystem services (ES). Maintaining or restoring multifunctionality in agricultural landscapes is considered an efficient solution to achieve sustainable agricultural production because multiple ES provided by a landscape can support both environmental protection and socio-economic benefits. Quantifying the provision of ES provides fundamental information to measure landscape multifunctionality and inform sustainable land management strategies. Although a large number of studies have been carried out to measure landscape multifunctionality and associated ES, comprehensive spatially explicit assessments at the farm scale are limited. OBJECTIVE: This research applies a wide range of spatial models, tools, and methods to spatially quantify the provision of multiple ES as well as the pattern of landscape multifunctionality in farmed landscapes. METHODS: To quantify the provision of multiple ES provided by the landscape, the bio-physical models provided by InVEST (e.g., Nutrient Delivery Ratio and Sediment Delivery Ratio models) and land use land cover-based assessments using spatial analysis tools in ArcGIS were employed. The Analytic Hierarchy Process was applied to calculate the landscape multifunctionality index which is an integration of multiple ES supply. Hot spot analysis using Getis Ord Gi* statistics was utilised to examine the spatial distribution of multiple ecosystem services. A hill country farm in New Zealand is chosen as a case study because it is a good example of a diverse landscape that is facing significant environmental issues due to intensive agricultural production. RESULTS AND CONCLUSIONS: Our study reveals that the provision of ES and the pattern of landscape multifunctionality is highly variable across the farm. Both positive and negative relationships among ES are found and the interactions between them are mainly reflected in three ES bundles: the agricultural land, the indigenous forest and wetlands, and the mixed land uses. Furthermore, our study demonstrates that the quality of landscape is significantly dependent on the landscape management goals and preferences of the farmer so involving them into the process of ES and landscape multifunctionality assessment at a farm scale is essential step to obtain more comprehensive results. SIGNIFICANCE: Results from this study enable important questions to be answered regarding the spatial variation of ES provision and how land use and land management goals relate to the value and quality of landscape multifunctionality. This can provide valuable information to design future multifunctional landscapes and inform decision making in relation to sustainable land use management. Graphical abstract: Unlabelled Image Highlights: Spatially-explicit assessment of landscape multifunctionality and ecosystem services at farm scale were carried out. The pattern of landscape multifunctionality and ecosystem services is highly variable across the farmed landscapes. Interaction between ecosystem services is complex and strongly associated to levels of landscape simplification. Landscape multifunctionality is dependent on the management goals and preferences of landowner. Results from this study can provide important basis to design future multifunctional landscapes.